2022
DOI: 10.1111/epi.17315
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and epilepsy in multiple sclerosis, aquaporin 4 antibody‐positive neuromyelitis optica spectrum disorder, and myelin oligodendrocyte glycoprotein antibody‐associated disease

Abstract: Seizure is one of the manifestations of central nervous system inflammatory demyelinating diseases, which mainly include multiple sclerosis (MS), aquaporin 4 antibody‐positive neuromyelitis optica spectrum disorder (AQP4‐NMOSD), and myelin oligodendrocyte glycoprotein antibody‐associated disease (MOGAD). Acute symptomatic seizures secondary to MS/AQP4‐NMOSD/MOGAD occur in the acute phase of the diseases, and are more frequent in MOGAD. In contrast, recurrent nonprovoked seizures, mainly attributed to autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 140 publications
(506 reference statements)
0
6
0
Order By: Relevance
“…Reduced AQPs expression has been reported under pathological conditions ( Markou et al, 2022 ), including brain edema after stroke or trauma ( Papadopoulos et al, 2002 ; Clément et al, 2020 ; Dadgostar et al, 2022 ), neurological diseases ( Yang et al, 2011 ; Alvestad et al, 2013 ; Li et al, 2022 ), cancer progression and metastasis ( Lan et al, 2022 ), and inflammation. Of note, AQP1 and AQP4 are reported to be downregulated in the choroid plexus and the ependyma, respectively, of spontaneously hypertensive rat, as a putative compensatory mechanism to reduce the cerebrospinal fluid (CSF) production and volume ( Carnero Contentti and Correale, 2021 ; González-Marrero et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced AQPs expression has been reported under pathological conditions ( Markou et al, 2022 ), including brain edema after stroke or trauma ( Papadopoulos et al, 2002 ; Clément et al, 2020 ; Dadgostar et al, 2022 ), neurological diseases ( Yang et al, 2011 ; Alvestad et al, 2013 ; Li et al, 2022 ), cancer progression and metastasis ( Lan et al, 2022 ), and inflammation. Of note, AQP1 and AQP4 are reported to be downregulated in the choroid plexus and the ependyma, respectively, of spontaneously hypertensive rat, as a putative compensatory mechanism to reduce the cerebrospinal fluid (CSF) production and volume ( Carnero Contentti and Correale, 2021 ; González-Marrero et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MOG-IgG has recently been associated with cortical encephalitis and seizures [ 20 ]. Seizures can arise in isolation in cases of single-antibody disorders and are also more frequently observed in male patients [ 1 , 21 , 22 ]. It has been reported in some rare cases that anti-NMDAR encephalitis and demyelinating diseases can coexist in the same patient while developing serological markers of autoimmune diseases and demyelinating (MOG abs), while we summarize the cases of seizures present in the course of the MNOS [ 3 , 7 16 ] in (see Supplementary file 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, they found that anti-NMDAR abs seemed to contribute to cortical destruction and seizures in MOG-IgG patients. Specific MRI abnormalities are associated with acute symptomatic seizures in MOGAD [ 22 ], mainly including unilateral/bilateral cortical T2/fluid attenuation inversion recovery (FLAIR) high-signal lesions, leptomeningeal enhancement, etc., with unilateral cortical T2/FLAIR high-signal lesions (FLAMES) being more likely to have seizures. FLAMES has different radiologic manifestations and may show bilateral cortical and meningeal lesions that are different from the common manifestations [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This issue was observed in stable seizures, drug-resistant seizures, generalized seizures, focal seizures and multi-focal seizures. The thickness of nerves ending in the retina was reduced and optic neuropathies such as visual, Neuromyelitis Optica Spectrum Disorder (NMOSD) (20) and optic neuritis were affected by seizure attacks (21). Visual acuity and contrast sensitivity are reduced under the in uence of these attacks (22), which deprive individuals of normal vision both in children and adults.…”
Section: Discussionmentioning
confidence: 99%